DIMORFISME SEKSUAL DAN NISBAH KELAMIN IKAN ARWANA {Scleropages spp.) [Sexual dimorphism and sex ratio and of asian arwana (Scleropages spp.)] - Agus H. Tjakrawidjaja (Jurnal Iktiologi Indonesia, 2006)
Preliminary study of biological reproduction aspects of Asian Arwana (S. jardinii and S. formosus) particularly sexual-dimorphism and sex-ratio of gender is very important as a base for captivity breeding. Up to the present, it is difficult to identify the sex identity of these Asian Arwanas that lead the difficulties in making sex-ratio description. The relible sex-ratio in captive breeding would increase the production. The result of this research would be useful for reference in the identification of the gender of Asian Arwanas.